STRUCTURAL CHANGE AND ECONOMIC GROWTH IN UKRAINE - SHOVKUN, Inna (Economy and Sociology, 2021)
Deep structural shifts have been the leading feature of the modern world. The study considers the parameters and causes of structural change in the Ukrainian economy, as well as the relationship between structural change on the one hand, and labor productivity and economic growth on the other. The study shows that the accelerated reduction of the industrial sector, its technological simplification and narrowing the variety of industries were the key features of the structural changes model that occurred in Ukraine's economy after the global financial crisis. This was accompanied by increased dominance of the tertiary sector and the growth of the primary sector. Such a trend of structural shifts is not able to generate the necessary boost of economic growth. Comparison of parameters and trends of structural changes in Ukraine’s economy and in a comparable group of countries and the world as a whole shows that the changes in the structure of Ukraine’s economy were more intensive, but did not create sufficient potential for sustainable economic growth. The author analyzes the gaps in labor productivity between economic activities and sectors of Ukraine’s economy, as well as changes in their dynamics, which leads to the conclusions about the relationship between the rates of technological development of different sectors of Ukraine’s economy and the gradual slowdown of the already imperfect technological development of this country’s industry. Using the apparatus of econometric modeling, the author evaluates the dependence of the dynamics of GDP growth on the change of the indices of GVA in the sectors of this country’s economy.